The Modified Ghost Method for Compressible Multi-Medium Interaction with Elastic-Plastic Solid (Communications in Computational Physics, 2017)
In this work, a robust, consistent, and coherent approach, termed as ModifiedGhost Method (MGM), is developed to deal with the multi-medium interactionwith elastic-plastic solid. This approach is simple to implement and keeps the solversintact, and can handle multi-medium problems which involve various media includinggas, liquid and solid. The MGM is first validated by two-dimensional (2D) casesand then is applied to study the interaction between elastic-plastic solid structure andthe underwater explosion. The development of the wave system is described and analyzed.Furthermore, two kinds of complex solid structure subjected to underwaterexplosion are simulated. Finally, a complex solid structure immersed in water subjectedto underwater explosion is simulated and analyzed. The numerical experimentsshow the viability, effectiveness and versatility of the proposed method which is ableto accurately predict the wave pattern at various interfaces.